Peran Kebijakan Pendidikan Inklusif dalam Meningkatkan Kualitas Sumber Daya Manusia - Mindariati, Mindariati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to analyze the role of inclusive education policies in improving the quality of human resources (HR) in Indonesia. The main focus of this research is on government policies that support inclusion in the education sector and their impact on access, participation, and learning outcomes for students with special needs. A qualitative descriptive method was employed, utilizing in-depth interviews with teachers, school principals, and policymakers from several inclusive schools in urban and rural areas. A total of 15 participants from various educational levels were involved in the study. The findings indicate that inclusive education policies positively contribute to enhancing educational access for students with special needs; however, challenges remain regarding resource availability and teacher training. Another positive impact observed is the increased social interaction and tolerance between regular students and those with special needs, which ultimately contributes to the overall improvement of HR quality. This study suggests that specialized training for teachers and the enhancement of educational facilities, particularly in remote areas, should be prioritized in efforts to strengthen the implementation of inclusive policies. Future research recommendations include exploring strategies for improving teacher capacity and developing more equitable inclusive educational infrastructure. Inclusive policies play a crucial role in creating quality human resources that are competitive and prepared to face global challenges.